The Potential of Smartphones on the Use of Experiential Learning Based Electronic Modules in Concierge Learning for Vocational High School - Winandari, Anita; Sutimin, Leo Agung; Rejekiningsih, Triana; Qodr, Taufiq Subhanul; Mulyasari, Dini Wahyu (Universitas Muhammadiyah Surakarta, 2022)
Technology literacy is a manifestation of a person's psychological response to everything related to technology. This is evidenced by the development of technology, namely the use of smartphones in various activities, one of which is in learning activities. However, there are weaknesses in the development of technology, for example the existence of teachers who have not been optimal in responding to technological developments which of course have an adverse impact on the learning process, so that improvements are needed in every learning system that leads to improving the quality of education. This study was conducted to identify the potential use of smartphones in facilitating student learning, especially in achieving the success of concierge learning materials in vocational high schools. This type of research is descriptive qualitative research. The research subjects were students majoring in tourism in class XII of a vocational high school with a total of 140 students. Data collection methods in this study were surveys and interviews using questionnaires and interview guidelines as research instruments. Data analysis was carried out in four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that there is a great opportunity for the use of smartphones in the learning process, especially in vocational high school concierge subjects. It is known that the use of smartphones by students is most dominantly used for things other than learning. To change the condition of students so that they are more comfortable using smartphones for learning, the researchers want to make experiential learning-based electronic module teaching materials more creative, innovative and interesting with features that include not only text, images, audio but practical videos. The conclusion of this study is that an electronic module based on experiential learning has great potential for the use of smartphones to make it easier for students to learn concierge at vocational high schools.